Development of Students' Psychological Flexibility Instruments: Islamic Perspectives - Ratnasari, Devi; Mamat Supriatna; Maria Oktasari; Mila Yunita (Tebuireng: Journal of Islamic Studies and Society, 2024)
This research aims to develop an instrument of psychological flexibility of students based on an Islamic perspective. The research uses a method of instrument development with a descriptive quantitative method. Data collection was carried out through psychological flexibility instruments in Islamic perspective students with 168 respondents. The instrument of psychological flexibility in students was developed based on the theory in Islamic psychology developed by the figures Al Ghazali, Ibn Sina, and Ibn Arabi. The results of the field test of the psychological flexural instrument were analyzed using the RASCH measurement model and Winstep software. Based on the results of the Item Fit Order Test, it is known that of the 60 items, the results of the Item and Person Reliability Test are in the ideal range (+0.5 logit to +1.5 logit) which is 0.95 and 0.88 which are in the very good category and meet the measurement requirements. In addition, the results of the Unidimensionality Test showed good unidimensionality (25.5%), where the raw variance index was above the threshold of 20%. This indicates that this instrument can accurately measure students' psychological flexibility. The results of this study can be considered in the use of psychological flexibility instruments among students, which can then be continued with the formulation of the right guidance and counseling model in increasing psychological flexibility.